Digital platform-based learning communication model at Tunas Unggul Junior High School Bandung - Hadiniyati, Ghina; Supratman, Lucy Pujasari (Manajemen Komunikasi, 2025)
In the digital era, educational communication has undergone innovations through digital platforms in digital technology-based schools. Tunas Unggul Junior High School, or SMP Tunas Unggul, a Global Interactive School in Bandung, emphasizes technology in its learning models for all students. This study aims to describe the digital technology-based learning communication model communicated by the SMP Tunas Unggul Bandung teachers to students across all classes. The research used a qualitative method with a case study approach, wherein data were collected through interviews and observations, with researchers directly engaging in the classroom activities of teachers and students. The findings indicate that the learning communication implemented at Tunas Unggul Bandung is interactive and based on digital technology, involving various verbal and nonverbal symbols. Teachers utilized interactive media such as Canva and a Learning Management System. The interactive learning communication between teachers and students at SMP Tunas Unggul Bandung has served as a means to build bonds between teachers and students, ensuring that all stakeholders adopt digital media-based learning well. Its implementation has proven to improve the quality of learning, one of the indicators being the noticeable improvement in learning outcomes experienced directly by the students. The findings of this study are expected to serve as practical suggestions for communication processes in the education sector, particularly at equivalent levels. In the future, it is hoped that more research in learning communication, mainly digital platform-based learning, will enrich the literature of Communication Science in education.